MUNICIPALIDAD Y CIUDADANÍA TENSIONES EN LA CIUDAD DE SAN RAMÓN - Guido Cruz, Francisco; Castro Sánchez, Silvia (Universidad de Costa Rica, 2023)
The urbanization process that takes place in Costa Rica in the last thirty years has various expressions.  In that context, this work explains the way in which municipalities, as local governments, change in order to satisfy the new demands of the inhabitants of urban centers that change as well.  This article also analyzes the municipalities’ performance from the citizens’ viewpoint.  In addition, it presents a discussion on how the citizens themselves evaluate their own participation in urban affairs.  The city of San Ramón is the case study that illustrates this discussion.